Implementation of the Crossword Puzzle Method in Social Studies Learning on Students Learning Outcomes - Fatimah, Siti; Tetep; Dahlena, Alni (SAHUR Journal, 2023)
Education is basically a conscious effort to develop the potential of students optimally. In learning social sciences, there are still many who consider it saturated learning and lack of interest by students so that it has an impact on student learning outcomes. One of the efforts to overcome this is the need for innovation and creative learning to package or deliver social studies subject matter so that learning activities become effective. One of them is using the crossword puzzle method. The purpose of this study was to determine the application of the crossword puzzle method in social studies learning to social studies learning outcomes. This type of research uses a quantitative approach with a quasi-experimental method with a pre-test and post-test nonequivalent control group design. The population of this study were students of class VIII, SMPN 3, Tarogong Kidul. Samples were taken by the purposive sampling technique with one experimental class and one control class. The instruments used in this study were test question sheets and observation sheets. Based on the results of the statistical analysis conducted, the initial abilities of the two groups resulted in the same abilities. Meanwhile, for the final test results, the Asymp.Sig.2-tailed value is 0.000 and is 0.05, meaning 0.000 <0.05, then Ho is rejected. It can be concluded that there are significant differences or learning using effective methods to be applied. The response of students to the crossword puzzle learning method used in the experimental class resulted in a very good response.